Pengaruh Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung Holaa Cafe Di Gresik - Aulia Aufa Diana; Rois Arifin; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine and explain the effect of product quality, price and service quality on the decisions of visitor satisfaction with Holaa Cafe in Gresik. This research is a quantitative type of research. The method used is multiple linear regression. The sampling technique uses the formula from Solvin with the calculation results of 75 samples. To solve the problems in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously. Variables of Product Quality, Price and Service Quality have a significant simultaneous effect on the Decisions of Holaa Cafe Visitors in Gresik. And there is a partial influence between product quality, price and service quality on the decisions of visitor satisfaction with Holaa Cafe in Gresik. Keywords: Product Quality, Price and Service Quality on Visitor Decisions